Bauran Pemasaran Jasa Pendidikan MI Muhammadiyah Program Khusus Kartasura - Rochmatun, Amin; , Minsih, S.Ag., M.Pd (2017)
This study aims to describe the marketing education service mix of MI Muhammadiyah Program Khusus Kartasura and obstacles and solutions in the application of marketing mix. This study is a qualitative research with phenomenology design. Data collection techniques using interviews, observation, and documentation. Data validity using triangulation of source and technique. Data analysis using Miles and Huberman model which consist of three stages that is data reduction, data presentation, and conclusion. The result of the research shows that 1) marketing education service mix of MI Muhammadiyah Program Khusus Kartasura consists of 7P, namely: a) Product (product), service products offered is to create students to develop their talents and practice the teachings of Islam. The program options offered are class fullday, tahfidz class, and SME class (Science, Mathematic and English);b) Price, price of education services based on the cost of school operational needs; c) Place, in a strategic location, accessible to both private and public transportation and close to the center of economic activity; d) Promotion (promotion), promotions made by advertising through various media, visiting TK-TK, and public relations activities such as takjil on the roa ; e) People (human resources), human resources consists of 28 teachers, 8 special escort teachers, 10 education personnel. The quality of human resources MI Muhamamdiyah Special Program Kartasura always be concerned with the existence of teacher learning programs, internship programs in advanced schools, seminars and recruitment through selection tests; f) Pshycal evidence (physical evidence), facilities and infrastructure at MI Muhammadiyah Program Khusus Kartasura adequate and support the activities of teaching and learning process; g) Process (process), using curriculum KTSP with multiple intelligence approach, has 23 extracurricular, some support programs and habituation of Islamic activity, 2) The barrier experienced is the price offered is considered expensive by some society and teacher difficulties in dividing the time between promotion with teacher agenda. The solution of these obstacles is to provide cost relief for the underprivileged and submit promotional activities to teachers who have time constraints.